Online e-mail marketing systém - Šmigura, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce je zaměřena na analýzu požadavků reklamní agentury na vytvoření systému pro online rozesílání e-mailových kampaní. Následné zhodnocení současného stavu se stává společně s výsledkem analýzy požadavků důležitým podkladem pro sestavení návrhu řešení a samotnou implementaci plně funkčního systému.

The subject of this Bachelor’s thesis is focused on an analysis of promotional agency’s requirements concerned with producing a system for online sending of e-mail campaigns. The subsequent evaluation of the current situation becomes together with a result of the analysis of requirements a relevant foundation in formulating a scheme for the solution and for the realization of the fully functional system.
Online E-mail Marketing System
Keywords: E-mail marketing; nástroj; HTML e-mail; webová aplikace; PHP; MySQL; E-mail marketing; tool; HTML e-mail; web application; PHP; MySQL